2019
DOI: 10.1115/1.4042250
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tip Leakage Flow in Spike-Type Rotating Stall Inception

Abstract: This paper describes the role of tip leakage flow in creating the leading edge separation necessary for the onset of spike-type compressor rotating stall. A series of unsteady multipassage simulations, supported by experimental data, are used to define and illustrate the two competing mechanisms that cause the high incidence responsible for this separation: blockage from a casing-suction-surface corner separation and forward spillage of the tip leakage jet. The axial momentum flux in the tip leakage flow deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…As well as a lower total pressure ratio, low pressure ratio fans are distinguished by reduced rotor inlet relative Mach numbers, typically below 1.4 at the tip and with subsonic relative inflow towards the hub. Analysis of single-stage, low hub-to-tip ratio subsonic compressors (Pullan, et al, 2015;Hewkin-Smith, et al, 2019) and transonic compressors (Hah, et al, 2006;Kim, et al, 2019) observe spike-type stall inception, or the absence of significant low-frequency disturbance preceding stall. Hewkin-Smith, et al (2019) attributed the sudden drop in pressure rise from local sectors of the rotor row to either spillage of tip leakage flow ahead of the leading edge, or separation from the suction surface within the rotor passage.…”
Section: Fan and Compressor Stall With Distorted Inflowmentioning
confidence: 99%
“…As well as a lower total pressure ratio, low pressure ratio fans are distinguished by reduced rotor inlet relative Mach numbers, typically below 1.4 at the tip and with subsonic relative inflow towards the hub. Analysis of single-stage, low hub-to-tip ratio subsonic compressors (Pullan, et al, 2015;Hewkin-Smith, et al, 2019) and transonic compressors (Hah, et al, 2006;Kim, et al, 2019) observe spike-type stall inception, or the absence of significant low-frequency disturbance preceding stall. Hewkin-Smith, et al (2019) attributed the sudden drop in pressure rise from local sectors of the rotor row to either spillage of tip leakage flow ahead of the leading edge, or separation from the suction surface within the rotor passage.…”
Section: Fan and Compressor Stall With Distorted Inflowmentioning
confidence: 99%
“…Hewkin-Smith et al in Ref. [11] showed how sweep and lean changes the distribution of the axial momentum in a tip leakage jet. By increasing the axial momentum of the jet or pushing its distribution rearward, it was possible to change the route to tip separation from a tip leakage dominated mechanism to a corner separation dominated mechanism.…”
Section: Off-design Behavior Of Multistage Compressorsmentioning
confidence: 99%
“…Hewkin-Smith et al showed that the 3D design could change the route to tip separation in Ref. [11], but it cannot change the topology of the separation once it has occurred. Large discontinuities are still present in all of the designs, and so, cell behavior is always observed.…”
Section: Off-design Behavior Of Multistage Compressorsmentioning
confidence: 99%
“…The total momentum can be calculated by Equation 6and (7). Notice that the momentum here is not only on the slot openings, but also on the tip clearance plane.…”
Section: Figure 9 Axial Momentum Distributions On Tip Clearancementioning
confidence: 99%
“…(Nan, 2014) investigated the influence of circumferential grooves in Rotor 67 by analyzing the momentum of a specific control volume inside the grooves. Besides, the momentum distribution in the tip clearance is used as a criterion to evaluate the tip leakage flow strength (Cameron et al, 2013;Hewkin-Smith et al, 2019;Nan, 2014). For the circumferential grooves, the momentum flux makes the extension of stall margin linearly (Shabbir and Adamczyk, 2005;Ross et al, 2017).…”
Section: Introductionmentioning
confidence: 99%